1981
DOI: 10.1111/j.1348-0421.1981.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Clostridium difficile from the Feces and the Antibody in Sera of Young and Elderly Adults

Abstract: Attempts were made to isolate Clostridium difJicile from a total of 431 fecal specimens from 149 young and 213 elderly healthy adults, and 69 elderly adults with cerebrovascular disease but no gastrointestinal disease. C. difJicile was isolated from 49 specimens, and the frequency of isolation was 15.4% in healthy young adults, 7.0% in healthy elderly adults, and 15.9% in elderly adults with cerebrovascular disease. Thirty-four (about 70%) of the 49 C. difJicile strains isolated produced cytotoxin which was ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 18 publications
2
69
2
Order By: Relevance
“…Twenty toxigenic C. difficile strains isolated in this laboratory from healthy adults or patients with antibiotic-associated diarrhea (14) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty toxigenic C. difficile strains isolated in this laboratory from healthy adults or patients with antibiotic-associated diarrhea (14) were used.…”
Section: Methodsmentioning
confidence: 99%
“…C. djicile strains were cultivated on modified cycloserine-cefoxitin-fructose-agar (CCFA) plates (Nakamura et al, 1981) anaerobically for 48 h. Several colonies of each strain were transferred to a medium for subculture (see Tables 2-4) and incubated at 37 "C for 10 h. The culture was then diluted 1000-fold in pre-reduced 0.85% (w/v) NaCl and 0.1 ml of the diluted culture was inoculated in duplicate into test media. The cultures were incubated at 37 "C. Inoculation, …”
Section: Preparation Of Mediamentioning
confidence: 99%
“…9689, 17857, and 17859 from the American Type Culture Collection (ATCC) , Rockville, Md., U.S.A.; 35 toxigenic and 15 nontoxigenic strains from healthy adults; five toxigenic and eight nontoxigenic strains from patients receiving antibiotics without gastrointestinal complications; eight toxigenic strains from antibiotic-associated diarrhea patients, and five toxigenic strains from antibiotic-associated PMC patients. Most of these strains were previously described (12,13 Preparation of antigen for the agglutination test. Bacterial cell antigen was prepared from a 7-hr culture of C. difJicile strain grown in a medium containing 3% (wjv) proteose peptone no.…”
Section: Methodsmentioning
confidence: 99%
“…Feces from the vast majority of PMC patients contain a cytopathic toxin which is neutralized by Clostridium sordellii antitoxin, and toxigenic C. difficile at high concentrations. The authors (12) previously reported that a fairly high population of young and elderly adults of Japanese harbored C. difficile in their colonic flora without any deleterious effect and that the antibody against C. difficile toxin was present in most young adults but not in elderly adults. With respect to the pathogenesis of antibiotic-associated diarrhea or PMC, it is claimed that in the presence of antimicrobial agents, C. difficile might selectively grow and produce a cytopathic toxin causing diarrhea or PMC (1,4).…”
mentioning
confidence: 99%